A 1770MPa grade hot-rolled carbon wire rod for bridge cables and a manufacturing method thereof
The C-SI-MN high-carbon carbon component system and online salt strong are used to use hot-rolled carbonic carbon bars in the 1770MPA-level bridge cable to form an organization that is dominated by the warrior of the fire in the fire. The problem of high -intensity decline and high risk of fracture realizes the combination of high strength and high plasticity, which is suitable for manufacturing high -strength bridges and cables.
Patent Information
- Application Number
- CN202411356385.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing 1770MPa-grade bridge cable hot-rolled strips are susceptible to multidirectional stress damage in variable climate environments such as high temperature, low temperature, cold and humidity, thunderstorms, and strong winds, resulting in a decrease in strength, high risk of fracture, and insufficient tissue uniformity and plasticity. .
Adopt the C-SI-Mn high-carbon carbon component system, but the provincial CR element is treated with the temperature treatment of the online melting salt strong, so that the plate strip is used to warn with high temperature bead light body phase area, forming an organization that is mainly based on the fire of fire. , Combined with the slow cold technology of rollers, refine the carbon carbides, and improve the uniformity and plasticity of the tissue.
Effectively improved the overall strength and plasticity of the 1770MPA -level bridge and cables with hot -rolled carbon bars, reducing the risk of fracture, ensuring the stability of tissue uniformity and mechanical properties, and suitable for high -intensity bridge cable manufacturing.
Smart Images

Figure CN118854173B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled wire rods for bridge cables, and specifically relates to a hot-rolled carbon wire rod for 1770MPa-grade bridge cables and a manufacturing method thereof. Background Art
[0002] 1770MPa-grade bridge cables are mainly used as the main load-bearing structure of suspension bridges in China. They are made of wire rods through processes such as pickling, deep drawing with a large surface reduction rate, hot-dip galvanizing, and twisted braiding. They will serve for a long time in changeable climatic environments such as high temperature, low temperature, cold and humidity, thunderstorms, and strong winds. The cable body and anchors are extremely susceptible to multi-directional stress damage. Suspension bridges and other safe passage tools need to have extremely high safety. Therefore, wire rods are used as the base material of bridge cables, and the performance of the wire rods is extremely high. The existing 1770MPa grade hot-rolled wire rods for bridge cables are usually based on a high-carbon component system and are produced at high speed by a Stelmor air-cooled line. For example, patent CN101311288B discloses a 1770MPa grade bridge cable galvanized steel wire wire rod and a manufacturing method thereof, which adopts a C-Si-Mn-Cr component design, a C content of 0.85% to 0.9%, and a Stelmor line fast cooling method after rolling and spinning to obtain a wire rod structure of sorbite ≥ 90%, a tensile strength Rm of 1300 to 1400MPa, and a cross-sectional shrinkage rate Z ≥ 35%; Therefore, the 1770MPa grade bridge cable wire rod with lower manufacturing cost, higher plasticity and uniform organization still has the following technical difficulties:
[0003] 1. 1770MPa-class bridge cables require a stronger reinforcement component system than 1670MPa-class and lower bridge cables. In order to reduce material costs, after eliminating Cr alloy, the wire rod passes through the troostite phase region for a relatively short time during the continuous cooling process of the Stelmor air-cooled wire controlled cooling, making it difficult to obtain a higher proportion of troostite with refined structure, which will lead to a significant decrease in the strength of the wire rod. A larger area reduction rate is required to improve the strength of the wire rod during subsequent wire making, exacerbating the risk of wire breakage. At the same time, the hot-dip galvanizing process will lose a certain strength. Excessive deterioration of the wire rod strength has the risk of not reaching the final performance level.
[0004] 2. When the carbon content is greater than 0.77%, the segregation of elements intensifies. At the same time, the maximum cooling capacity of the Stelmor air-cooling line is limited. Even if it is cooled quickly, the wire rod takes a long time to pass through the secondary cementite and tertiary cementite. The secondary cementite precipitates in a network along the grain boundary. The large amount of tertiary cementite precipitation will coarsen the cementite particles, destroy the continuity of the organization, affect the uniformity and mechanical properties of the wire rod, especially seriously deteriorate the plasticity and toughness of the wire rod. Reducing the carbon content will not only reduce the strength of the wire rod, but also have limited improvement on the tertiary cementite and organizational uniformity, resulting in insufficient plasticity of the wire rod and increased fluctuations in mechanical properties. The wire rod will break due to crack expansion during the wire making process.
[0005] 3. In order to minimize the adverse effects of network carbides on high-carbon wire rods, although air cooling is used for rapid cooling, the wire is spread on the conveying roller after being spun into wire rods. When passing through the air cooling line, the fans are set at intervals. There are differences in air volume on the wire rod conveying path, the windward side and the leeward side of the wire rod. As the air cooling intensity increases further, this uncontrollable factor also leads to a large temperature difference in various parts of the wire rod, and the risk of abnormal structures such as bainite and martensite is high. The strengthening effect of carbon is often weakened due to the uncontrollable cooling rate during the cooling phase transformation process, and the austenite structure fails to fully transform into the troostite during the troostite phase transformation. In the late stage of controlled cooling during the continuous cooling process, the untransformed austenite structure will also have the risk of transforming into an abnormal structure, which seriously affects the uniformity and plasticity of the wire rod structure, resulting in a high risk of breakage of the wire rod during the processes of wire making, torsion, and braiding.
[0006] 4. Although the structure of the wire rod can be transformed into troostite during the Stelmor controlled cooling process, the maximum cooling rate can only reach about 10℃ / s, which makes it difficult to form a large degree of supercooling, resulting in coarse spacing between the formed troostite lamellae. The increase in lamella thickness increases the difficulty of melting and spheroidization. At the same time, during the continuous cooling process, the temperature of the wire rod after the troostite phase transformation is low, and the thermal power is insufficient. Therefore, the residual stress and dislocation density of the formed troostite structure are large, and the final plasticity is insufficient. In the subsequent multiple continuous cold drawing deformation wire making process, this deformation energy storage is accumulated, and the work hardening is obvious, which will further affect the wire drawing and torsion performance of the steel wire, causing the risk of fracture and affecting the yield rate of bridge cables. Summary of the invention
[0007] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a hot-rolled carbon wire rod for 1770MPa-grade bridge cables and a manufacturing method thereof, which can eliminate the Cr element, avoid abnormal martensite and bainite structures, improve the uniformity of the structure, take into account the strength and high plasticity of the wire rod, is suitable for the manufacture of 1770MPa-grade bridge cables, and can reduce the risk of breakage.
[0008] The technical solution adopted by the present invention to solve its technical problem is:
[0009] A method for manufacturing a 1770MPa grade hot-rolled carbon wire rod for bridge cables, the manufacturing method comprising:
[0010] The wire rod is produced by rolling according to the chemical composition of the hot-rolled carbon wire rod, and the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.71%~0.75%, Si: 0.15%~0.25%, Mn: 0.85%~0.95%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥920°C, it is subjected to an online molten salt strong isothermal treatment, so that the wire rod is cooled to the pearlite phase region at a cooling rate of ≥30°C / s to form a structure mainly composed of bainite, and isothermal tempering is performed to promote the melting of the bainite structure lamellae, and finally it is slowly cooled by a roller to produce a hot-rolled carbon wire rod with a microstructure including tempered bainite with a volume percentage of ≥96%, and the rest is a mixed structure composed of ferrite and fused bainite.
[0011] The chemical composition and mass percentage design basis of the above hot rolled carbon wire rod include:
[0012] (1) Carbon: As an economical and effective strengthening element, carbon can ensure the high strength of bridge cables. Increasing the carbon content in steel is conducive to the formation of more cementite lamellae in the troostite structure. The refined troostite lamellae have better deformation properties and are beneficial to deep drawing wire making. However, too high a carbon content will make it more difficult to control the composition segregation during the solidification process of the alloy, increase the risk of forming network cementite precipitated along the grain boundary and generating abnormal structures such as bainite and martensite. Therefore, in order to take into account the rigorous use test of 1770MPa bridge cables and the control of wire rod structure uniformity, the carbon content can be appropriately reduced to reduce the composition segregation. Combined with the wire rod after spinning, it is subjected to online molten salt strong isothermal treatment to further reduce the risk of network cementite precipitation, avoid the network cementite causing a sharp decrease in the plastic toughness of the material, and inhibit the peak precipitation of tertiary cementite, thereby refining the cementite carbide, improving the uniformity of the structure and the utilization value of carbon, which is beneficial to the refinement of troostite lamellae and isothermal tempering. Therefore, the mass percentage of carbon is controlled to be 0.71%~0.75%.
[0013] (2) Silicon: Si is often added to steel as a deoxidizer during the smelting process. Si dissolved in the ferrite phase can strengthen the material and inhibit the precipitation of cementite, reduce the loss of steel wire strength, make the cementite thinner, and accelerate the diffusion of carbon, which is beneficial to the transformation of the troostite structure to micro-spheroidization to form tempered troostite during isothermal tempering. However, Si is a ferrite strengthening element and can reduce the austenite phase area. Too much silicon will increase the graphitization tendency of C and reduce the toughness of steel, which is not conducive to the subsequent galvanizing process. Therefore, in order to take into account the high strength and toughness of the steel wire rod for bridge cables and facilitate the control of the wire rod structure, the mass percentage of Si is controlled to 0.15%~0.25%.
[0014] (3) Manganese: Mn is often added as a deoxidizer in the steelmaking process. At the same time, it converts S in the molten steel into MnS to reduce hot brittleness and ensure the smooth progress of the rolling process. As an austenite-forming element, Mn can expand the austenite phase region, making it easier to quickly pass the third cementite peak precipitation temperature during the strong isothermal treatment of the molten salt online and enter the pearlite phase region to form a troostite structure dominated by fine lamellar spacing. The strength and wear resistance of the wire rod are increased by solid solution strengthening, and the mechanical properties of the bridge cable steel wire are improved. However, when the Mn content is too high, it will aggravate the tendency of grain coarsening and component segregation, increase the hardenability of the wire rod, move the C curve downward, and increase the risk of quenching structure in the wire rod. Therefore, in order to take into account the high strength and toughness of the steel wire rod for bridge cables and facilitate the regulation of the wire rod structure, the mass percentage of Mn is controlled to be 0.85%~0.95%.
[0015] (4) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.
[0016] The above manufacturing method is based on the C-Si-Mn high-carbon carbon component system. Appropriately reducing the carbon content and eliminating the Cr element can reduce material costs, the difficulty of segregation control and the adverse effects of Cr on the toughness of the wire rod. The C, Si and Mn ratios are reasonably adjusted to expand the austenite phase region, which is beneficial to refining cementite carbides, controlling the troostite transformation and inhibiting the bainite transformation. Combined with the online molten salt strong isothermal treatment directly through the salt bath after spinning:
[0017] 1. Compared with the existing Stelmor rapid cooling after spinning, there are still higher levels of network carbides and a large amount of precipitated tertiary cementite due to high carbon segregation and cooling rate limitation. The present invention uses molten salt treatment to utilize the high heat exchange capacity of molten salt to quickly cool the wire rod from the austenitization high temperature after spinning, increase the cooling rate to suppress the brittleness caused by the precipitation of network carbides along the grain boundaries, and suppress the peak precipitation of tertiary cementite at 700-800°C, thereby refining the cementite carbides and improving the uniformity of the organization, so as to improve the overall strength and plasticity of the wire rod.
[0018] 2. Compared with the existing Stelmor rapid cooling and continuous cooling after spinning, the risk of abnormal tissue is high and it is difficult to effectively control the uniformity of tissue. On the one hand, the present invention can effectively reduce the temperature difference of the wire rod because the molten salt can be coated on the surface of the wire rod for rapid and uniform heat exchange when the wire rod passes through the molten salt. In the process of the wire rod quickly entering the pearlite phase region from the high-temperature austenite state, it can avoid local overcooling and enter the bainite or even martensite phase region, thereby forming a bainite structure dominated by fine lamellar spacing. On the other hand, the present invention can keep the wire rod consistent with the molten salt temperature during online molten salt strong isothermal treatment, and perform isothermal treatment in the high-temperature pearlite phase region for a longer time instead of slow cooling. The wire rod stays in the pearlite phase region for a longer time, which can make the tissue fully transformed into the bainite structure, and can also avoid the transformation of the untransformed austenite structure to the abnormal structure during the subsequent roller slow cooling process, thereby effectively avoiding the occurrence of bainite and martensite abnormal tissues to increase the brittleness of the wire rod, improve the uniformity of the tissue, and reduce the difference in mechanical properties.
[0019] 3. Compared with the existing Stelmor continuous rapid cooling and continuous cooling after spinning, which can only obtain the structure with insufficient troostitization rate, insufficiently fine lamellae and large dislocation density, the present invention undergoes online molten salt strong isothermal treatment. On the one hand, rapid cooling can make the formed troostite lamellae finer, which is beneficial to melting and transformation to micro-spheroidized structure, while maintaining the pearlite phase region for a longer time, so that the high-temperature austenite is transformed into more troostite, and the proportion of ferrite is reduced, thereby improving the matrix strength and compensating for the strength loss caused by reducing carbon content and eliminating Cr element. On the other hand, with long-term exposure to pearlite, the strength loss of the matrix is reduced. High temperature isothermal treatment is carried out in the light body phase region to provide more thermal power for the tempering of troostite, so that the newly formed troostite structure gradually undergoes the melting transformation of the troostite lamellar layer, and the carbides are further spheroidized to toughen the structure, reducing the stress and dislocation density of the structure, forming tempered troostite and fused troostite. In the further roller slow cooling process, the high temperature state of the wire rod after leaving the salt bath is used to slowly cool down to avoid the deterioration of plasticity caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further spheroidization of carbides, improves the softening effect of the wire rod, and finally realizes the regulation of the wire rod structure and ensures the matching of the strength and plasticity of the wire rod.
[0020] Since the alloy composition and content of hot-rolled carbon wire rod are relatively small, an appropriate soaking temperature of the heating furnace can be selected and the time in the furnace can be controlled to avoid the risk of burning and decarburization. In a preferred embodiment, before rolling, the steel billet is heated in a heating furnace with a soaking temperature of ≤1130°C and a time in the furnace of ≤3h.
[0021] Since a large number of fine lamellar tempered troostite structures can be formed through online molten salt strong isothermal treatment, the spinning temperature does not need to be too low. Therefore, the rolling temperature can be appropriately increased to increase the rolling speed and reduce the wear on the rolling mill, which is beneficial to efficient production. At the same time, a larger reduction distribution is combined to promote dynamic re-approximation of the rolling process, refine the grains, and strengthen the matrix. In a preferred embodiment, during the rolling, the initial rolling temperature is 1080~1120℃, the initial rolling reduction is 25%~35%, the intermediate rolling temperature is 980~1030℃, the intermediate rolling reduction is 30%~35%, the final rolling temperature is ≥930℃, and the final rolling reduction is 25%~30%.
[0022] In a preferred embodiment, the molten salt temperature of the online molten salt strong isothermal treatment is 525~565℃, and the treatment time is 300~650s. The lower the molten salt temperature is, the finer the tempered troostite lamellae formed, the wire rod strength increases and the plasticity decreases. However, if the molten salt temperature is too low, there is a risk of bainite structure appearing and losing the plasticity of the wire rod. On the contrary, the higher the molten salt temperature is, the coarser the tempered troostite lamellae formed, which can provide more thermal power for high-temperature isothermal treatment to promote carbide spheroidization and matrix softening, the wire rod strength decreases and the plasticity increases. However, if the molten salt temperature is too high, pearlite structure is formed, and the proportion of ferrite increases, which will cause a large strength loss of the wire rod, which is not conducive to deep drawing and wire making of small-sized wire rods for bridge cables. At the same time, the online time of slow roller cooling is The time will also be extended, which is not conducive to efficient production; the longer the processing time, the better the toughening and softening effect of the wire rod, but if the processing time is too long, it will affect the production efficiency of the wire rod and increase the production energy consumption. Excessive softening of the wire rod structure is not conducive to the production of high-strength bridge cables. On the contrary, the shorter the processing time, the lower the melting of the troostite lamellar layer, the softening effect, and the plasticity of the wire rod. However, if the processing time is too short, the carbide fails to transform into the spheroidized structure, and even the wire rod fails to fully transform into the troostite structure, which will lead to a decrease in the proportion of tempered troostite and the risk of abnormal tissue precipitation, which is not conducive to the control of strength and plasticity properties and tissue uniformity. Therefore, the molten salt temperature and processing time can be further controlled to promote the troostite phase transformation and isothermal tempering, and regulate the strength and plasticity of the wire rod.
[0023] Since the temperature of the wire rod drops from the high-temperature austenite temperature of the spinning to the pearlite phase temperature, the molten salt circulation rate can be further controlled to reduce the molten salt temperature rise, while avoiding unnecessary increase in energy consumption and cost caused by excessive molten salt circulation rate. In a preferred embodiment, the molten salt circulation rate of the online molten salt strong isothermal treatment is 380~480t / h, and the molten salt temperature rise is ≤10℃.
[0024] In a preferred embodiment, the roller slow cooling controls the wire rod to be slowly cooled at a cooling rate of 0.3~0.5℃ / s to below 300℃ for coiling. At this cooling rate, the wire rod can be slowly cooled from the pearlite phase temperature, and the continuation of high temperature promotes microstructure toughening, increases the degree of carbide spheroidization of tempered troostite, reduces microstructure stress and dislocation density, makes the microstructure stress distribution uniform, and further improves the softening effect.
[0025] In a preferred embodiment, the roller slow cooling is closed by an insulation cover, and the hot air from the online molten salt strong isothermal treatment is passed into the insulation cover. The wire rods are transported by rollers into the insulation cover, so that the heat energy generated during the molten salt treatment can be recycled, making the roller slow cooling temperature control more stable and reducing production energy consumption.
[0026] A hot-rolled carbon wire rod for a 1770 MPa grade bridge cable, wherein the hot-rolled carbon wire rod is manufactured by any of the above-mentioned methods for manufacturing the hot-rolled carbon wire rod for a 1770 MPa grade bridge cable.
[0027] The hot-rolled carbon wire rod is based on the C-Si-Mn high-carbon carbon component system, without adding Cr components, which can appropriately reduce the material cost and obtain a mixed structure composed of mainly tempered troostite structure and very small amounts of ferrite and fused troostite. Compared with the existing troostite wire rod structure of more than 90%, the tempered troostite structure accounts for a higher proportion, and the tempered troostite retains the characteristics of finer troostite lamellae and higher strength than the pearlite structure, which can make up for the strength loss caused by reducing the carbon content and not adding Cr components. At the same time, after the troostite structure is tempered, the carbide is transformed into spheroidization to form tempered troostite and fused troostite, and the organizational stress and dislocation density are improved. While taking into account the strength of the wire rod, the plasticity and toughness of the wire rod can be greatly improved. At the same time, the refinement control of cementite carbides, the full transformation of the wire rod to tempered troostite, and the absence of bainite and martensite abnormal structures also effectively improve the uniformity of the wire rod structure, thereby comprehensively and effectively reducing the risk of wire rod fracture during wire making, torsion, and braiding.
[0028] The finer the spacing between tempered troostite lamellae, the higher the strength of the wire rod and the lower the plasticity. However, if the spacing between tempered troostite lamellae decreases further, there is a risk of the appearance of bainite structure and loss of wire rod plasticity and structural uniformity. If the spacing between tempered troostite lamellae increases further, there is a risk of a decrease in the proportion of tempered troostite, loss of wire rod strength, and unfavorable for efficient production. In a preferred embodiment, the spacing between tempered troostite lamellae is 90~125nm.
[0029] In a preferred embodiment, the network carbide level of the hot-rolled carbon wire rod is level 0, which can eliminate the adverse effects of the network carbide on the uniformity and plasticity of the wire rod and improve the strengthening effect of carbon.
[0030] The high-carbon component system used in high-strength bridge cables makes it more difficult to control the fluctuations in the mechanical properties of the wire rod. Since the tissue control of the present invention is more uniform and there is no abnormal tissue, in a preferred embodiment, the mechanical property difference of the hot-rolled carbon wire rod is ≤25MPa, which can effectively reduce the risk of wire breakage caused by mechanical fluctuations.
[0031] In a preferred embodiment, the diameter of the hot-rolled carbon wire rod is 12.5-15.0 mm, which has a smaller diameter specification, making it easier to obtain the target wire diameter after drawing, avoiding excessive loss of drawing hardening and plasticity during the process, and the tensile strength Rm is 1170-1220 MPa, and the cross-sectional shrinkage Z is 48%-54%. The wire rod has both high strength and significantly improved plasticity and toughness, which can effectively reduce the risk of fracture in the manufacture of 1770 MPa-level bridge cables.
[0032] Compared with the prior art, the beneficial effects of the present invention are at least:
[0033] (1) In view of the fact that 1770MPa-grade hot-rolled wire rods for bridge cables are usually produced at high speed by Stelmor air-cooling lines, it is difficult to effectively control the uniformity of the wire rod structure, and the risk of abnormal structure is high and the plasticity is insufficient, resulting in a high risk of breakage of the wire rod during the processes of wire making, torsion, and braiding. The manufacturing method of the present invention controls the wire rod from the high-temperature austenite state to the pearlite phase region through the design of carbon chemical composition combined with online molten salt strong isothermal technology, which can avoid network carbides, inhibit tertiary cementite, refine cementite carbides, and form a large amount of troostite structure at the same time. In the subsequent high-temperature isothermal process, the newly formed troostite structure gradually undergoes troostite lamellar melting transformation, which can effectively avoid the risk of abnormal structures such as bainite and martensite produced by C elements, and maximize the strengthening effect of carbon elements. Finally, it is further softened by slow roller cooling to improve the uniformity of the structure, thereby improving the overall strength and plasticity of the wire rod and reducing the fluctuation of mechanical properties. It has good industrial adaptability.
[0034] (2) Aiming at the current situation that the hot-rolled wire rod for 1770MPa bridge cables has insufficient uniformity and plasticity, and has a high risk of fracture during use, the present invention is based on a C-Si-Mn high-carbon carbon component system and does not add Cr components, which can appropriately reduce material costs. The microstructure type is a mixed structure composed of tempered troostite, ferrite, and fused troostite. The tempered troostite accounts for a higher proportion and has finer layers, which can maximize the strengthening effect of the carbon element and make up for the strength loss caused by reducing the carbon content and not adding Cr components. There is no abnormal structure and the structure is more uniform. The tempered state is used to control the high strength and plasticity of the wire rod to match the product, which can achieve a tensile strength of 1170~1220MPa, a cross-sectional shrinkage of 48%~54%, and a mechanical property difference of ≤25MPa. It is suitable for the manufacture of 1770MPa bridge cables and can effectively reduce the risk of wire rod fracture during wire making, torsion, and braiding, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0036] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;
[0037] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;
[0038] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION
[0039] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention. They are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention. They should not be construed as limiting the scope of the present invention, which is limited only by the appended claims. Embodiment 1:
[0040] A preferred embodiment of the method for manufacturing the 1770MPa grade hot-rolled carbon wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.71%, Si: 0.25%, Mn: 0.91%, P: 0.013%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method thereof is manufactured according to the process flow of rolling → spinning → online molten salt strong isothermal → roller slow cooling → coiling, specifically:
[0041] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled to avoid the risk of burning and decarburization. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 14mm through a rolling line. The appropriate rolling temperature and reduction ratio are used to control rapid rolling and refine the structure grain. Specifically: the heating furnace is heated according to the preheating section, heating section and soaking section program, and the soaking temperature is 1125°C. The furnace time is 3h, the initial rolling temperature is 1105℃, the initial rolling reduction is 27%, the intermediate rolling temperature is 1015℃, the intermediate rolling reduction is 31%, the final rolling temperature is 945℃, and the final rolling reduction is 27%; the wire-spinning process is used to convert the wire rods coming out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. Through the appropriate wire-spinning temperature, favorable conditions are created for the deformation nucleus of the sorbite phase. Specifically, the wire-spinning temperature is controlled to be 930℃.
[0042] The online molten salt strong isothermal process adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by rollers and quickly cooled to the molten salt temperature for online molten salt strong isothermal treatment, so that the wire rod is cooled to the pearlite phase region at a cooling rate of 35°C / s, the peak precipitation of tertiary cementite is suppressed, the cementite carbide is refined, and a troostite-based structure is formed. The troostite structure is mainly composed of fine lamellar spacing. In the subsequent high-temperature isothermal process, the carbide micro-spheroidization and gradual melting of the lamellae of the newly formed troostite structure are promoted, and the strength and plasticity matching of the wire rod is adjusted. Specifically: the molten salt temperature is 541°C, the processing time is 580s, the molten salt circulation volume is 450t / h, and the molten salt temperature rise is ≤10°C.
[0043] The roller slow cooling process is closed by a heat preservation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the heat preservation cover for slow cooling treatment to avoid plastic deterioration caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further spheroidization of carbides. Specifically: the hot air above the salt bath tank is passed into the heat preservation cover, and the wire rod is controlled to be slowly cooled to 295°C at a cooling rate of 0.35°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled carbon wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 1 shown.
[0044] Comparative Example 1:
[0045] A method for manufacturing hot-rolled carbon wire rod, the difference between the manufacturing method and embodiment 1 is that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor strong air cooling → Stelmor weak air cooling, specifically: the soaking temperature is 1050°C, the furnace time is 4h, the initial rolling temperature is 1030°C, the intermediate rolling temperature is 930°C, the final rolling temperature is 870°C, and the spinning temperature is 850°C; the Stelmor strong air cooling adopts an air volume of 200,000 m per fan 3 / h, open 1~6# fans at 90%, and cool the wire rod to 620℃ at a cooling rate of 9.2℃ / s. The Stelmore weak air cooling adopts an air volume of 200,000m 3 / h, open 7~11# fans at 15%, cool the wire rod to 295℃ at a cooling rate of 2.7℃ / s, and obtain the finished wire rod after it comes off the line.
[0046] Comparative Example 2:
[0047] A method for manufacturing a hot-rolled carbon wire rod, the manufacturing method of which differs from that of Example 1 in that: the soaking temperature is 1065°C, the furnace time is 3.5h, the initial rolling temperature is 1050°C, the intermediate rolling temperature is 955°C, the final rolling temperature is 910°C, the spinning temperature is 890°C, and the finished wire rod is obtained after rolling off the line. Embodiment 2:
[0048] A preferred embodiment of the manufacturing method of the 1770MPa grade hot-rolled carbon wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.73%, Si: 0.19%, Mn: 0.91%, P: 0.013%, S: 0.012%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt strong isothermal → roller slow cooling → coiling, specifically:
[0049] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity, avoiding the risk of burning and decarburization. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 13mm through a rolling line, and the rapid rolling and refined structure grains are controlled by appropriate rolling temperature and reduction distribution. Specifically: the heating furnace is heated according to the preheating section, heating section and soaking section program, the soaking temperature is 1120℃, and at The furnace time is 2.5h, the initial rolling temperature is 1095℃, the initial rolling reduction is 30%, the intermediate rolling temperature is 1000℃, the intermediate rolling reduction is 33%, the final rolling temperature is 935℃, and the final rolling reduction is 28%; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. Through the appropriate wire-spinning temperature, favorable conditions are created for the deformation nucleus of the sorbite phase. Specifically: the wire-spinning temperature is controlled to be 925℃.
[0050] The online molten salt strong isothermal process adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by rollers and quickly cooled to the molten salt temperature for online molten salt strong isothermal treatment, so that the wire rod is cooled to the pearlite phase region at a cooling rate of 31°C / s, the peak precipitation of tertiary cementite is suppressed, the cementite carbide is refined, and a troostite-based structure is formed. The troostite structure is mainly composed of fine lamellar spacing. In the subsequent high-temperature isothermal process, the carbide micro-spheroidization and gradual melting of the lamellae of the newly formed troostite structure are promoted, and the strength and plasticity matching of the wire rod is adjusted. Specifically: the molten salt temperature is 552°C, the processing time is 430s, the molten salt circulation volume is 400t / h, and the molten salt temperature rise is ≤10°C.
[0051] The roller slow cooling process is closed by a heat preservation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the heat preservation cover for slow cooling treatment to avoid plastic deterioration caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further spheroidization of carbides. Specifically: the hot air above the salt bath tank is passed into the heat preservation cover, and the wire rod is controlled to be slowly cooled to 297°C at a cooling rate of 0.4°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled carbon wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.
[0052] Comparative Example 3:
[0053] A method for manufacturing hot-rolled carbon wire rod, which differs from Example 2 in that the wire rod is cooled to the pearlite phase region at a cooling rate of 35°C / s, the molten salt temperature is 520°C, the molten salt circulation rate is 520t / h, and the finished wire rod is obtained after it comes off the line.
[0054] Comparative Example 4:
[0055] A method for manufacturing a hot-rolled carbon wire rod, the manufacturing method of which is different from that of Example 2 in that the molten salt temperature is 590° C., and a finished wire rod is obtained after the wire rod is rolled off the production line. Embodiment 3:
[0056] A preferred embodiment of the method for manufacturing the 1770MPa grade hot-rolled carbon wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.75%, Si: 0.15%, Mn: 0.85%, P: 0.015%, S: 0.012%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt strong isothermal → roller slow cooling → coiling, specifically:
[0057] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled to avoid the risk of burning and decarburization. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 12.5mm through a rolling line. The appropriate rolling temperature and reduction ratio are used to control rapid rolling and refine the structure grain. Specifically: the heating furnace is heated according to the preheating section, heating section and soaking section program, and the soaking temperature is 1115 ℃, the furnace time is 2h, the initial rolling temperature is 1080℃, the initial rolling reduction is 35%, the intermediate rolling temperature is 980℃, the intermediate rolling reduction is 35%, the final rolling temperature is 930℃, and the final rolling reduction is 30%; the wire-spinning process is used to convert the wire rods leaving the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the roller table and transported along the roller table. Through the appropriate wire-spinning temperature, favorable conditions are created for the deformation nucleus of the sorbite phase. Specifically: the wire-spinning temperature is controlled to be 920℃.
[0058] The online molten salt strong isothermal process adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by rollers and quickly cooled to the molten salt temperature for online molten salt strong isothermal treatment, so that the wire rod is cooled to the pearlite phase region at a cooling rate of 33°C / s, the peak precipitation of tertiary cementite is suppressed, the cementite carbide is refined, and a troostite-based structure is formed. The troostite structure is mainly composed of fine lamellar spacing. In the subsequent high-temperature isothermal process, the carbide micro-spheroidization and gradual melting of the lamellae of the newly formed troostite structure are promoted, and the strength and plasticity matching of the wire rod is adjusted. Specifically: the molten salt temperature is 525°C, the processing time is 650s, the molten salt circulation volume is 480t / h, and the molten salt temperature rise is ≤10°C.
[0059] The roller slow cooling process is closed by a heat preservation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the heat preservation cover for slow cooling treatment to avoid plastic deterioration caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further spheroidization of carbides. Specifically: the hot air above the salt bath tank is passed into the heat preservation cover, and the wire rod is controlled to be slowly cooled to 288°C at a cooling rate of 0.3°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled carbon wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.
[0060] Comparative Example 5:
[0061] A method for manufacturing hot-rolled carbon wire rod, the manufacturing method of which is different from that of Example 3 in that the online molten salt strong isothermal treatment time is 240s, and the finished wire rod is obtained after going offline.
[0062] Comparative Example 6:
[0063] A method for manufacturing hot-rolled carbon wire rod, the manufacturing method of which is different from that of Example 3 in that the online molten salt strong isothermal treatment time is 760s, and the finished wire rod is obtained after going offline. Embodiment 4:
[0064] A preferred embodiment of the manufacturing method of the 1770MPa grade hot-rolled carbon wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.73%, Si: 0.22%, Mn: 0.95%, P: 0.014%, S: 0.013%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt strong isothermal → roller slow cooling → coiling, specifically:
[0065] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity, avoiding the risk of burning and decarburization. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 15mm through a rolling line, and the rapid rolling and grain refinement of the structure are controlled by appropriate rolling temperature and reduction distribution. Specifically: the heating furnace is heated according to the preheating section, heating section and soaking section program, and the soaking temperature is 1130°C. The furnace time is 3h, the initial rolling temperature is 1120℃, the initial rolling reduction is 25%, the intermediate rolling temperature is 1030℃, the intermediate rolling reduction is 30%, the final rolling temperature is 950℃, and the final rolling reduction is 25%; the wire-spinning process is used to convert the wire rods coming out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. Through the appropriate wire-spinning temperature, favorable conditions are created for the deformation nucleus of the sorbite phase. Specifically, the wire-spinning temperature is controlled to be 935℃.
[0066] The online molten salt strong isothermal process adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by rollers and quickly cooled to the molten salt temperature for online molten salt strong isothermal treatment, so that the wire rod is cooled to the pearlite phase region at a cooling rate of 30°C / s, the peak precipitation of tertiary cementite is suppressed, the cementite carbide is refined, and a troostite-based structure is formed. The troostite structure is mainly composed of fine lamellar spacing. In the subsequent high-temperature isothermal process, the carbide micro-spheroidization and gradual melting of the lamellae of the newly formed troostite structure are promoted, and the strength and plasticity matching of the wire rod are adjusted. Specifically: the molten salt temperature is 565°C, the processing time is 300s, the molten salt circulation volume is 380t / h, and the molten salt temperature rise is ≤10°C.
[0067] The roller slow cooling process is closed with an insulation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the insulation cover for slow cooling treatment to avoid plastic deterioration caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further spheroidization of carbides. Specifically: hot air above the salt bath tank is passed into the insulation cover, and the wire rod is controlled to be slowly cooled to 284°C at a cooling rate of 0.5°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled carbon wire rod product is obtained after packaging and storage.
[0068] Comparative Example 7:
[0069] A method for manufacturing a hot-rolled carbon wire rod, which differs from Example 4 in that: the method is manufactured according to the process flow of rolling → spinning → online molten salt strong isothermal → air cooling, and the air cooling process adopts the method of opening a heat preservation cover, conveying the wire rod out of the salt bath tank by a roller, controlling the wire rod to be cooled to 284°C at a cooling rate of 1.8°C / s, and obtaining the finished wire rod after it comes off the line.
[0070] The organization and performance testing of the wire rods obtained in the above embodiments and comparative examples include: the tensile test is carried out according to "GB-T228.1-2021 Metal Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional shrinkage rate; the organization is tested according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: 2 circles of wire rod are taken 5m away from the end of the coil, and each circle of wire rod is divided into 8 sections on average with the overlap area as the base point, and 1 tensile specimen is taken from each section. The extreme difference in strength of the tensile specimen after the tensile test is the mechanical property same circle difference, and the comparison results obtained are shown in Table 1 below:
[0071] Table 1. Comparison of the microstructure and properties of different wire rod compositions and manufacturing methods
[0072]
[0073] From the comparison results of Example 1 and Comparative Example 1, it can be seen that compared with the high-speed production by the Stelmor air-cooled line, it is difficult to effectively control the uniformity of the wire rod structure, and the risk of abnormal structure is high, the troostitization rate is not high enough, the interlamellar spacing, the residual stress of the structure and the dislocation density are large, and ultimately the strength and plasticity are insufficient without adding Cr components. The present invention is based on the C-Si-Mn high-carbon carbon component system, with a higher proportion of tempered troostite and finer lamellae, which can maximize the strengthening effect of the carbon element and make up for the strength loss caused by reducing the carbon content and not adding Cr components. At the same time, it can avoid network carbides, inhibit tertiary cementite, and refine cementite carbides. The tempered state is used to regulate the high strength and plasticity matching of the wire rod, especially the plasticity of the wire rod can be significantly improved.
[0074] It can be seen from the results of Examples 1 to 4 that the microstructure type is a mixed structure composed of tempered troostite, ferrite, and fused troostite, which can achieve a product tensile strength of 1170 to 1220 MPa, a cross-sectional shrinkage rate of 48 to 54%, and a mechanical property difference of ≤25 MPa. It is suitable for the manufacture of 1770 MPa-level bridge cables and can effectively reduce the risk of wire rod breakage during wire making, torsion, and braiding.
[0075] From the comparison results of Example 1 and Comparative Example 2, it can be seen that by selecting an appropriate spinning temperature, a greater degree of supercooling can be formed through online molten salt strong isothermal treatment, which is beneficial to the formation of a large number of fine lamellar tempered troostite structures. At the same time, the rolling temperature can be appropriately increased to increase the rolling speed and reduce the wear on the rolling mill.
[0076] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the lower the molten salt temperature, the finer the tempered bainite lamellae formed, the wire rod strength increases and the plasticity decreases, but if the molten salt temperature is too low, there is a risk of bainite structure appearing and loss of wire rod plasticity.
[0077] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the higher the molten salt temperature, the coarser the tempered troostite lamellae formed, which can provide more thermal power for high-temperature isothermal treatment to promote carbide spheroidization and matrix softening, and the strength of the wire rod decreases and the plasticity increases. However, if the molten salt temperature is too high, the proportion of ferrite increases, which will cause a large strength loss of the wire rod.
[0078] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the shorter the online molten salt strong isothermal treatment time, the lower the melting of the troostite lamellar, the lower the softening effect, and the lower the plasticity of the wire rod. However, if the treatment time is too short, the carbide fails to transform into a spheroidized structure, which will lead to a decrease in the proportion of tempered troostite, which is not conducive to the control of the strength-plasticity and mechanical properties.
[0079] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the longer the online molten salt strong isothermal treatment time, the better the toughening and softening effect of the wire rod. However, if the treatment time is too long, it will affect the wire rod production efficiency. Excessive softening of the wire rod structure is not conducive to the production of high-strength bridge cables.
[0080] From the comparison results of Example 4 and Comparative Example 7, it can be seen that during the slow cooling process on the roller, the high temperature state of the wire rod after leaving the salt bath is utilized to slowly cool down the wire rod to avoid plastic deterioration caused by rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and further spheroidization of carbides, thereby improving the softening effect of the wire rod.
[0081] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention, and they are not intended to limit the scope of protection of the present invention. For example, the steel billet is obtained by sequentially performing converter smelting, refining, and continuous casting processes. Any equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing a 1770MPa grade hot-rolled carbon wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The wire rod is produced by rolling according to the chemical composition of the hot-rolled carbon wire rod, wherein the chemical composition and mass percentage of the hot-rolled carbon wire rod are: C: 0.71%~0.75%, Si: 0.15%~0.25%, Mn: 0.85%~0.95%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥920°C, it is subjected to an online molten salt strong isothermal treatment to make the wire rod The wire rod is cooled to the pearlite phase region at a cooling rate of ≥30°C / s to form a structure mainly composed of troostite and isothermally tempered to promote the melting of the troostite structure lamellae, and finally slowly cooled by a roller to be a hot-rolled carbon wire rod having a microstructure including a mixed structure consisting of tempered troostite with a volume percentage of ≥96% and the rest being ferrite and fused troostite; the molten salt temperature of the online molten salt strong isothermal treatment is 525-565°C, and the treatment time is 300-650s.
2. The method for manufacturing the 1770MPa grade hot-rolled carbon wire rod for bridge cables according to claim 1, characterized in that: Before the rolling, the steel billet is heated in a heating furnace, the soaking temperature is ≤1130°C, and the time in the furnace is ≤3h.
3. The method for manufacturing the 1770MPa grade hot-rolled carbon wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling temperature is 1080-1120°C, the initial rolling reduction is 25%-35%, the intermediate rolling temperature is 980-1030°C, the intermediate rolling reduction is 30%-35%, the final rolling temperature is ≥930°C, and the final rolling reduction is 25%-30%.
4. The method for manufacturing the 1770MPa grade hot-rolled carbon wire rod for bridge cables according to claim 1, characterized in that: The molten salt circulation rate of the online molten salt strong isothermal treatment is 380-480 t / h, and the molten salt temperature rise is ≤10°C.
5. The method for manufacturing the 1770MPa grade hot-rolled carbon wire rod for bridge cables according to claim 1, characterized in that: The roller slow cooling controls the wire rod to be slowly cooled to below 300° C. at a cooling rate of 0.3-0.5° C. / s for coiling.
6. The method for manufacturing the 1770MPa grade hot-rolled carbon wire rod for bridge cables according to claim 5, characterized in that: The roller slow cooling adopts a heat preservation cover to close, and the hot air of the online molten salt strong isothermal treatment is introduced into the heat preservation cover, and the wire rod is transported into the heat preservation cover by the roller.
7. A 1770MPa grade hot-rolled carbon wire rod for bridge cables, characterized in that: The hot-rolled carbon wire rod is manufactured by the manufacturing method of the hot-rolled carbon wire rod for 1770MPa grade bridge cables as described in any one of claims 1 to 6.
8. The 1770MPa grade hot-rolled carbon wire rod for bridge cables according to claim 7, characterized in that: The interlamellar spacing of the tempered bainite is 90-125 nm, the network carbide grade of the hot-rolled carbon wire rod is grade 0, and the mechanical property difference is ≤25 MPa.
9. The 1770MPa grade hot-rolled carbon wire rod for bridge cables according to claim 7, characterized in that: The hot-rolled carbon wire rod has a diameter of 12.5-15.0 mm, a tensile strength of 1170-1220 MPa, and a cross-sectional shrinkage of 48%-54%.
Citation Information
Patent Citations
Wire rod for producting1770Mpa bridge cable galvanized steel wire and method for manufacturing same
CN101311288B
High-carbon cold heading steel wire rod for 14.9-grade non-quenched and tempered bolt and manufacturing method of high-carbon cold heading steel wire rod
CN118639120A
Cold forging steel high-carbon hot-rolled wire rod for 15.9-grade bolt and manufacturing method of cold forging steel high-carbon hot-rolled wire rod
CN118639124A